The Effectiveness of Soy Milk Administration In Reducing Menopausal Symptoms Based On The Menopause Rating Scale (MRS) In Mothers In Ciseureh Village Purwakarta Regency In 2026 - Aan Rosanti; Ika Mariska; Bunga Anggita Sagia (CV. Inara, 2026)
Menopause is a physiological process in women characterized by the permanent cessation of menstruation due to decreased ovarian function. Hormonal changes that occur during menopause often cause various physical, psychological, and urogenital complaints that can reduce a woman's quality of life. One non-pharmacological approach to reducing menopausal symptoms is the administration of soy milk containing the phytoestrogen isoflavone. This study aimed to determine the effectiveness of soy milk in reducing menopausal symptoms in postmenopausal women.This study used a pre-experimental design with a one-group pretest-posttest approach. The research sample consisted of 33 respondents selected using the random sampling technique.purposive sampling according to inclusion and exclusion criteria. Measurement of menopausal complaints was carried out using a questionnaire.Menopause Rating Scale (MRS) before and after soy milk intervention for 4 weeks. Data were analyzed using a paired t-test with a significance level of α = 0.05.The results of the study showed that the average score of menopausal complaints before the intervention was 14.52 and after the intervention decreased to 9.52. The results of the statistical analysis usingPaired t-test obtained a p-value = 0.000 (p < 0.05), which shows that there is a significant effect of giving soy milk on reducing menopausal complaints in menopausal women. The conclusion of this study is that soy milk is effective in reducing menopausal symptoms in postmenopausal women. Soy milk can be used as an alternative non-pharmacological therapy to help reduce menopausal symptoms and improve the quality of life of postmenopausal women.